A low-closure high-broken-membrane polyolefin diaphragm and a preparation method thereof
Patent Information
- Application Number
- CN202611218702.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-12
- Publication Date
- 2026-10-27
AI Technical Summary
[0003]本发明的目的是针对现有技术存在的单组分聚烯烃材料难以兼顾低闭孔与高破膜温度、直接添加低熔点组分易削弱高温支撑能力、无机颗粒与有机基体界面相容性差易导致团聚以及拉伸成型时易引发微孔缺陷并破坏孔隙连通性等问题,提供一种界面结合牢固、内部微观结构均匀,兼具灵敏的低闭孔阻断功效及优异的高温抗形变能力与机械强度的一种低闭孔高破膜聚烯烃隔膜及其制备方法
1.本发明的聚烯烃隔膜较传统材料更好地兼顾了较低闭孔温度与较高破膜温度。低熔点芯层受热迅速熔融闭孔,外层硅网络与硅藻土协同提供坚固支撑,有效缓解了传统隔膜敏锐闭孔与高温抗形变难以两全的技术矛盾。
Smart Images

Figure CN122992278A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of battery polymer materials technology, specifically to a low-closed-pore, high-breakage polyolefin separator and its preparation method. Background Technology
[0002] Polyolefin membranes are core components in electrochemical energy storage devices, primarily serving to isolate the positive and negative electrodes and ensure normal ion transport. In practical applications, thermal runaway poses a significant safety hazard to these devices. An ideal membrane should rapidly close its micropores to block reactions when temperatures rise abnormally, and maintain its physical integrity even under high thermal shock, preventing short circuits caused by direct contact between the positive and negative electrodes. This requires the membrane to possess both a low pore-closing temperature and a high membrane rupture temperature. However, existing single-component polyolefin materials often struggle to achieve both. In pursuit of low pore-closing activity, the overall heat resistance and mechanical strength of the material are typically sacrificed. To mitigate this contradiction, a common approach is to introduce low-melting-point polymers or inorganic particles into the matrix. While unilaterally incorporating low-melting-point components can trigger pore closure earlier, it inevitably weakens the membrane's high-temperature support capacity, leading to a significant decrease in the membrane rupture temperature. However, the approach of adding inorganic particles through physical blending to improve thermal stability faces the insurmountable challenge of interfacial compatibility. After all, there is a natural difference in interfacial tension between inorganic materials and organic polymers, which makes it easy for inorganic particles to agglomerate during melt blending, making it difficult to form a uniformly dispersed structural network within the matrix. This uneven dispersion and weak interfacial bonding cause microscopic stress concentration during membrane stretching, resulting in uneven microporous structure development and even pore defects. Under complex stress conditions, free inorganic particles easily detach from the matrix, failing to provide effective skeletal support and disrupting the original pore connectivity within the membrane, thus affecting the material's ability to absorb and retain electrolytes. Therefore, current technology has significant shortcomings in coordinating polymer flexibility, the heat resistance and support of inorganic components, and the multiphase interfacial bonding state, making it difficult to prepare a highly reliable membrane that can both sensitively close pores and resist high-temperature deformation. Summary of the Invention
[0003] The purpose of this invention is to address the problems existing in the prior art, such as the difficulty in achieving both low closed-cell and high membrane breakage temperature in single-component polyolefin materials, the tendency of directly adding low-melting-point components to weaken high-temperature support, the poor interfacial compatibility between inorganic particles and organic matrix leading to agglomeration, and the tendency to cause micropore defects and disrupt pore connectivity during stretching molding. The invention provides a low-closed-cell, high-breakage polyolefin membrane and its preparation method, which features a strong interfacial bond, uniform internal microstructure, sensitive low-closed-cell blocking effect, and excellent high-temperature deformation resistance and mechanical strength.
[0004] To achieve the above objectives, the technical solution adopted by the present invention is: a low-closed-cell, high-breakage polyolefin diaphragm, wherein the solid matrix of the diaphragm is composed of the following components in parts by weight: 50-80 parts of high-density polyethylene, 10-25 parts of in-situ coated low-melting-point polyethylene / silica composite particles, 5-15 parts of diatomaceous earth, 0.5-2 parts of silane coupling agent, 0.5-2 parts of antioxidant, and 1-3 parts of lubricant.
[0005] Furthermore, the in-situ coated low-melting-point polyethylene / silica composite particles are prepared from raw materials comprising the following parts by weight: 100 parts of low-melting-point polyethylene resin with a melting point of 120-125℃, 3-5 parts of vinyltrimethoxysilane, 0.03-0.08 parts of benzoyl peroxide, 0.3-0.8 parts of polyvinylpyrrolidone, 40-60 parts of tetraethyl silicate, 2-4 parts of ammonia water with a mass concentration of 25%, 400-600 parts of anhydrous ethanol, and 80-150 parts of deionized water.
[0006] Furthermore, the method for preparing the in-situ coated low-melting-point polyethylene / silica composite particles is as follows: S1. Cryogenic phase change pulverization: The low-melting-point polyethylene resin is pre-cooled in a liquid nitrogen environment for 20-40 minutes to reduce the material temperature to below -150℃. Then, cryogenic impact pulverization and airflow classification are performed to collect low-melting-point polyethylene core layer particles with D50 of 0.20-0.40μm and D90 of no more than 0.80μm. S2, Low activation energy interface grafting: 100 parts of low melting point polyethylene core layer microparticles obtained in S1, 3-5 parts of vinyltrimethoxysilane and 0.03-0.08 parts of benzoyl peroxide are added to a high-speed mixing system. Under nitrogen protection, the mixture is sheared at a speed of 3000-5000 rpm for 30-45 minutes, and the material temperature is controlled at 80-90℃. This allows vinyltrimethoxysilane to undergo free radical-initiated interface grafting on the surface of the low melting point polyethylene core layer microparticles, resulting in activated microparticles with hydrolyzable silane groups on the surface. S3. Stable interfacial dispersion: The activated microparticles are added to a mixture of anhydrous ethanol and deionized water, wherein the volume ratio of anhydrous ethanol to deionized water is 4:1, and 0.3-0.8 parts of polyvinylpyrrolidone are added. After ultrasonic dispersion at 25-35℃ for 20-40 min, the mixture is stirred at 600-1000 rpm for 30-60 min to obtain a stable dispersion. S4. Low-temperature in-situ copolymerization coating: Add 40-60 parts of tetraethyl silicate to the stable dispersion dropwise over a period of 30-60 minutes. After the addition is complete, add 2-4 parts of ammonia water with a mass concentration of 25% to adjust the pH of the system to 8.5-9.5. Perform ultrasonic-assisted stirring at 35-45°C for 4-6 hours to hydrolyze and condense tetraethyl silicate to form a silica network. Then, through the silane grafting layer on the surface of the activated microparticles, a continuous silica coating layer is grown in situ on the surface of the low-melting-point polyethylene core layer. S5. Thermal densification treatment: The reaction solution obtained in S4 is spray-dried, with an inlet air temperature of 85-95℃ and an outlet air temperature of 55-70℃, to obtain primary composite particles; then the primary composite particles are placed at 85℃ and a vacuum degree of less than -0.09MPa for 20-24 hours to further dehydrate, condense and densify the silica coating layer, to obtain in-situ coated low-melting-point polyethylene / silica composite particles.
[0007] Furthermore, the high-density polyethylene has a density of 0.950-0.960 g / cm3 and a melt flow rate of 0.1-0.5 g / 10 min at 190°C and 2.16 kg.
[0008] Furthermore, the diatomaceous earth has a median diameter of 8-14 μm, an oil absorption rate of 80%-160%, and a moisture content of ≤0.5% by mass.
[0009] Furthermore, the antioxidant is a compound of pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate] and tris(2,4-di-tert-butyl)phosphite in a mass ratio of 1:1.
[0010] Furthermore, the lubricant is a compound of calcium stearate and ethylene bis-stearamide mixed in a mass ratio of 1:2.
[0011] Furthermore, the silane coupling agent is 3-(methacryloyloxy)propyltrimethoxysilane.
[0012] Furthermore, the low-melting-point polyethylene resin in S1 is metallocene polyethylene with a density of 0.910-0.925 g / cm3.
[0013] Furthermore, the low-temperature free radical initiator in S2 is azobisisobutyronitrile or benzoyl peroxide.
[0014] A method for preparing a low-closed-cell, high-breakage polyolefin separator includes the following steps: (1) Material mixing: Add high-density polyethylene, in-situ coated low-melting-point polyethylene / silica composite particles, diatomaceous earth, silane coupling agent, antioxidant and lubricant to a high-speed kneader and mix at 110-120℃ for 10-15 minutes.
[0015] (2) Melt extrusion: The mixed material is added to a twin-screw extruder, and after melt blending, extrusion and casting, a base film is obtained.
[0016] (3) Annealing treatment: Anneal the base film in a hot air oven at 105-115℃ for 1-2 hours.
[0017] (4) Biaxial stretching: The annealed base film is stretched longitudinally and transversely in sequence.
[0018] (5) Heat setting: The stretched film is heat set at 120-130℃, and the diaphragm is obtained after cooling and winding.
[0019] Furthermore, the temperature of each zone of the twin-screw extruder in step (2) is set as follows: feeding zone 160-170℃, melting zone 190-210℃, metering zone 200-220℃, and die head zone 195-205℃. In step (4), the longitudinal stretching temperature is 85-95℃ and the stretching ratio is 4-6 times; the transverse stretching temperature is 100-110℃ and the stretching ratio is 3-5 times.
[0020] Furthermore, the aforementioned low-closed-pore, high-rupture polyolefin separator can be used as a structural component or manufacturing process for inactive parts of electrochemical batteries, excluding fuel cells.
[0021] Furthermore, the aforementioned low-closed-pore, high-breakage polyolefin separator can be used in the manufacture of lithium-ion batteries.
[0022] Furthermore, the aforementioned low-closed-cell, high-breakage polyolefin diaphragm may contain any one of vinyl elastomers or metallocene polyolefins.
[0023] This invention achieves thermal safety management and physical support for the diaphragm by constructing a multiphase synergistic solid matrix structure. The core of this mechanism is the uniformly dispersed in-situ coated low-melting-point polyethylene / silica composite particles within the matrix. When abnormal temperatures occur inside the energy storage device, the low-melting-point resin in the core layer of the composite particles undergoes phase change melting first, flowing and filling the surrounding pore channels, promptly blocking ion transport and achieving a sensitive pore-closure response. The in-situ grown silica on the outer layer, in synergistic with the diatomaceous earth in the system, constructs a robust inorganic support network that resists the shrinkage and creep deformation of the polymer matrix at higher temperatures, maintaining the morphological integrity of the diaphragm and thus increasing the material's membrane breakage temperature. The in-situ copolymerization coating process effectively improves the interfacial tension difference between the inorganic and organic phases. Combined with the interfacial bridging of the silane coupling agent, this allows the modified material to be uniformly dispersed within the high-density polyethylene skeleton during blending and extrusion. This structure avoids the drawbacks of inorganic particles easily agglomerating and undergoing interfacial delamination in traditional physical blending methods. During the biaxial stretching molding stage, it can guide the uniform distribution of internal stress and promote the formation and connection of regular micropores. While ensuring the original mechanical strength and flexibility of the matrix, it effectively resolves the contradiction between the performance of sensitive closed pores and high-temperature deformation resistance of a single material.
[0024] Compared with the prior art, the beneficial effects of the present invention are: 1. The polyolefin separator of the present invention achieves a better balance between lower pore-closure temperature and higher membrane rupture temperature compared with traditional materials. The low-melting-point core layer melts rapidly upon heating to close the pores, while the outer silicon network and diatomaceous earth work together to provide robust support, effectively alleviating the technical contradiction of traditional separators that are difficult to balance sensitive pore closure with high-temperature deformation resistance.
[0025] 2. This invention improves the interfacial tension difference between the inorganic phase and the organic matrix through in-situ co-condensation coating and coupling modification. The modified microparticles are more uniformly dispersed in the matrix, avoiding the agglomeration and delamination phenomena that are easily caused by traditional physical additives. During stretching and molding, it guides the uniform distribution of stress and ensures the connectivity of micropores.
[0026] 3. Based on the constructed stable multiphase interface, the membrane produced by this invention can still maintain excellent tensile strength and flexibility after the inorganic support component is introduced; this can effectively overcome the problem of mechanical property degradation caused by the release of inorganic substances in traditional modification schemes, and effectively improve the mechanical reliability of the material under complex stress environment. Attached Figure Description
[0027] Figure 1 This is a SEM image of the in-situ coated low-melting-point polyethylene / silica composite particles prepared in Example 1 of this invention.
[0028] Figure 2The XPS full spectrum of the in-situ coated low-melting-point polyethylene / silica composite particles prepared in Example 1 of this invention is shown.
[0029] Figure 3 The image shows the FTIR infrared spectrum of a low-closed-pore, high-breakage polyolefin membrane prepared in Example 1 of this invention. Detailed Implementation
[0030] The technical solution of the present invention will now be clearly and completely described with reference to the accompanying drawings. Obviously, the described embodiments are merely some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0031] Preparation Example 1 Preparation of in-situ coated low-melting-point polyethylene / silica composite particles: 1. Raw material components by weight: Low-melting-point polyethylene resin: 100 parts. The low-melting-point polyethylene resin is metallocene polyethylene with a density of 0.918 g / cm³. 3 The melt flow rate was 1.0 g / 10 min; the metallocene polyethylene resin, model Exceed1018.Rk, was purchased from ExxonMobil Chemicals Ltd.
[0032] Vinyltrimethoxysilane: 4 parts.
[0033] Benzoyl peroxide: 0.05 parts.
[0034] Polyvinylpyrrolidone: 0.5 parts.
[0035] Tetraethyl silicate: 50 parts.
[0036] Ammonia solution with a mass concentration of 25%: 3 parts.
[0037] Anhydrous ethanol: 400 parts.
[0038] Deionized water: 125 parts.
[0039] Liquid nitrogen: appropriate amount.
[0040] Nitrogen: appropriate amount.
[0041] 2. Preparation method: S1. Cryogenic Phase Change Pulverization: Take 100 parts of the above-mentioned low-melting-point polyethylene resin and pre-cool it in a liquid nitrogen environment for 30 minutes to lower the material temperature to below -150℃; then perform cryogenic impact pulverization in a low-temperature embrittlement state, and perform airflow classification on the pulverized material to collect low-melting-point polyethylene core layer particles with D50 of 0.30μm and D90 not greater than 0.75μm. In this step, pre-cooling with liquid nitrogen transforms the low-melting-point polyethylene from a flexible state to an embrittled state, which facilitates the acquisition of core layer particles with concentrated particle size and relatively intact surfaces.
[0042] S2. Low Activation Energy Interface Grafting: Take 100 parts of the low-melting-point polyethylene core layer microparticles obtained in S1, add 4 parts of vinyltrimethoxysilane and 0.05 parts of benzoyl peroxide, and mix evenly under nitrogen protection. Control the system temperature at 85℃ and the shearing speed at 4000 rpm, and continuously process for 40 min to allow benzoyl peroxide to generate free radicals under heating conditions, which initiates the interface grafting reaction of vinyltrimethoxysilane on the surface of the low-melting-point polyethylene core layer microparticles. After the reaction is complete, cool the material to below 35℃ to obtain activated microparticles with hydrolyzable silane groups on the surface.
[0043] S3. Interface Dispersion Stability: 400 parts of anhydrous ethanol and 125 parts of deionized water were mixed to form an alcohol-water mixture. The activated microparticles obtained in S2 were added to the alcohol-water mixture, followed by 0.5 parts of polyvinylpyrrolidone. The mixture was dispersed at 30°C for 30 min, and then stirred at 800 rpm for 45 min to obtain a uniform and stable dispersion of activated microparticles. In this step, polyvinylpyrrolidone adsorbs onto the surface of the activated microparticles, which can reduce the tendency for secondary agglomeration between microparticles and provide a stable dispersion interface for the subsequent hydrolysis and polycondensation of tetraethyl silicate.
[0044] S4. Low-temperature in-situ copolymerization coating: 50 parts of tetraethyl silicate were added dropwise to the activated microparticle dispersion obtained in S3, with the addition time controlled at 45 min. After the addition was completed, 3 parts of 25% ammonia water were added to adjust the pH of the system to 9.0, and the reaction temperature was controlled at 40℃. The reaction was stirred continuously for 5 h. During the reaction, tetraethyl silicate underwent hydrolysis and condensation under alkaline conditions to form a silica network structure. At the same time, the silane graft layer on the surface of the activated microparticles obtained in S2 participated in interfacial condensation, enabling the silica network to grow in situ on the surface of the low-melting-point polyethylene core layer, forming a composite coating structure with low-melting-point polyethylene as the core layer and silica network as the outer layer.
[0045] S5. Thermal densification treatment: The reaction dispersion obtained in S4 is dried, with the inlet air temperature controlled at 90℃ and the outlet air temperature at 62℃ to obtain primary composite particles. These primary composite particles are then placed at 85℃ and a vacuum degree less than -0.09MPa for 22 hours to further dehydrate, condense, and densify the silica coating layer, while simultaneously removing residual ethanol, moisture, and unreacted small molecules. After treatment, the particles are cooled to room temperature to obtain in-situ coated low-melting-point polyethylene / silica composite particles.
[0046] like Figure 1 As shown in the SEM image, the composite particles exhibit a near-spherical or quasi-spherical morphology. While some soft agglomeration exists between the particles, no obvious large hard agglomerates or flaky deposits were observed, indicating that the particles, after in-situ coating and dispersion stabilization treatment, possess good shape integrity and dispersibility. The particle surface is not completely smooth, exhibiting slight roughness and granular texture, which is consistent with the structural characteristics of the in-situ grown silica network on the outer side of the low-melting-point polyethylene core layer. This image can be used to demonstrate that the composite particles have a regular morphology, a relatively concentrated particle size distribution, and that the silica coating forms a relatively rough outer surface, which is beneficial for forming a more stable interfacial bond within the polyolefin membrane matrix.
[0047] like Figure 2 As shown, the XPS full spectrum clearly shows C1s, O1s, and Si2p related signals. The C1s peak mainly originates from the low-melting-point polyethylene core layer and the silane-grafted organic segments on the surface. The O1s and Si2p peaks correspond to Si-O-Si and Si-OH structures in the silica coating layer, indicating that a silicon-oxygen-containing inorganic phase has been successfully introduced onto the surface of the composite particles. The high intensity of the C peak in the spectrum indicates that the organic polyethylene component is still the main component. At the same time, the clear presence of Si and O signals indicates that the silica is not completely free or its content is too low, but rather forms a coating structure on the particle surface that can be detected by XPS. The baseline in the figure shows some fluctuations and is accompanied by a small number of weak impurity peaks, which is consistent with the signal characteristics of surface adsorbed water, residual dispersant, or trace inorganic impurities in actual XPS tests. Overall, it can be used to prove that silicon oxidation modification and in-situ silica coating have occurred on the surface of the low-melting-point polyethylene core layer.
[0048] Comparative Preparation Example 1 The preparation of in-situ coated low-melting-point polyethylene / silica composite particles was carried out by referring to the preparation method in Preparation Example 1, except that vinyltrimethoxysilane was replaced with an equal mass of methyltrimethoxysilane, and everything else remained the same as in Preparation Example 1.
[0049] Comparative Preparation Example 2 The preparation of in-situ coated low-melting-point polyethylene / silica composite particles was carried out according to the preparation method in Preparation Example 1, except that 50 parts of tetraethyl silicate were replaced with 72.1 parts of a nano-silica ethanol dispersion with a mass concentration of 20% based on the equivalent amount of silica. The nano-silica ethanol dispersion contained 14.42 parts of nano-silica and 57.68 parts of anhydrous ethanol. The rest remained the same as in Preparation Example 1.
[0050] Comparative preparation example 3 The preparation of in-situ coated low-melting-point polyethylene / silica composite particles was carried out by referring to the preparation method in Preparation Example 1, except that the low-melting-point polyethylene resin with a melting point of 122°C was replaced with an equal mass of conventional high-density polyethylene resin with a melting point of 135°C, and everything else remained the same as in Preparation Example 1.
[0051] The conventional high-density polyethylene resin was purchased from Dongguan Huibai Plastic Raw Materials Co., Ltd. Comparative preparation example 4 The preparation of in-situ coated low-melting-point polyethylene / silica composite particles was carried out by referring to the preparation method in Preparation Example 1, except that polyvinylpyrrolidone was replaced with an equal mass of sodium dodecyl sulfate, and everything else remained the same as in Preparation Example 1.
[0052] Comparative preparation example 5 The preparation of in-situ coated low-melting-point polyethylene / silica composite particles was carried out by referring to the preparation method in Preparation Example 1, except that benzoyl peroxide was replaced with an equal mass of anhydrous ethanol, and everything else remained the same as in Preparation Example 1.
[0053] Example 1 Preparation of a polyolefin membrane with low closed-cell and high membrane breakage: 1 part by weight of raw material components: 60 parts of high-density polyethylene, wherein the high-density polyethylene is SABIC ® HDPEB5429, high-density polyethylene, has a density of 0.954 g / cm³. 3 The melt flow rate at 190℃ and 2.16kg was 0.3g / 10min.
[0054] 15 parts of in-situ coated low-melting-point polyethylene / silica composite particles, wherein the in-situ coated low-melting-point polyethylene / silica composite particles are the product obtained in Preparation Example 1.
[0055] 10 parts diatomaceous earth.
[0056] One part of silane coupling agent, wherein the silane coupling agent is 3-(methacryloyloxy)propyltrimethoxysilane, i.e., KH-570.
[0057] One part of antioxidant, wherein the antioxidant is a compound of antioxidant 1010 and antioxidant 168 in a mass ratio of 1:1.
[0058] Two parts of lubricant, wherein the lubricant is a compound of calcium stearate and ethylene bis-stearamide in a mass ratio of 1:2; that is, 0.67 parts of calcium stearate and 1.33 parts of ethylene bis-stearamide.
[0059] 2. Preparation method: (1) Material mixing: High-density polyethylene was dried under vacuum at 70℃ for 4 hours; in-situ coated low-melting-point polyethylene / silica composite particles were dried under vacuum at 60℃ for 6 hours; diatomaceous earth was dried at 105℃ for 3 hours to reduce its moisture content to below 0.5%. After drying, the diatomaceous earth was cooled to below 60℃ for later use. 10 parts of the dried diatomaceous earth were added to a high-speed mixing system and premixed at 80℃ and 800rpm for 3 minutes; then 1 part of silane coupling agent KH-5701 was added to the diatomaceous earth by dropping for 5 minutes. After the dropping was completed, the mixture was continued at 80℃ and 1200rpm for 15 minutes to uniformly wet and adsorb the silane coupling agent onto the surface of the diatomaceous earth, thus obtaining pre-coupled diatomaceous earth. 60 parts of high-density polyethylene, 15 parts of in-situ coated low-melting-point polyethylene / silica composite particles, pre-coupled diatomaceous earth, 1 part of antioxidant, and 2 parts of lubricant were added to a high-speed kneading system and continuously mixed at 115°C for 12 minutes at a speed of 1500 rpm. After mixing, the mixture was cooled to below 60°C to obtain a premix.
[0060] (2) Melt Extrusion: The obtained premix is added to a twin-screw extrusion system for melt blending, extrusion, and casting. The twin-screw extrusion temperatures are set sequentially as follows: feed zone 165℃, melt zone 200℃, metering zone 210℃, and die head zone 200℃; the screw speed is 80 rpm, the feed rate is 0.5 kg / h, and the average residence time of the material in the screw is controlled to be 2-4 min. The extruded melt is cast onto the surface of the cooling roller through a coat hanger die, the die lip gap is controlled to be 0.35 mm, the cooling roller temperature is controlled to be 35℃, and the traction speed is 0.8 m / min, resulting in an unstretched base film with a thickness of 95-120 μm.
[0061] (3) Annealing treatment: The obtained unstretched base film was placed in a hot air oven and annealed at 110°C for 1.5 hours, and then naturally cooled to room temperature.
[0062] (4) Biaxial stretching: The annealed base film is subjected to longitudinal stretching and transverse stretching in sequence. The longitudinal stretching temperature is controlled at 90℃, the longitudinal stretching ratio is 5 times, and the stretching rate is controlled at 50% / min; the transverse stretching temperature is controlled at 105℃, the transverse stretching ratio is 4 times, and the stretching rate is controlled at 30% / min.
[0063] (5) Heat setting: The obtained biaxially oriented film was heat-set at a fixed width of 125℃ for 8 minutes. After heat setting, the film was cooled to 25℃ and then wound flat under a tensile tension of 8N to obtain a low-closed-cell, high-breakage polyolefin separator. The resulting separator had a thickness of 18±2μm, a smooth surface, and no obvious crystal points, pores, streaks, or inorganic filler agglomeration points.
[0064] like Figure 3 As shown in the spectrum, approximately 2915 cm⁻¹ -1 and 2848cm -1 A distinct absorption peak for both -CH2- asymmetric and symmetric stretching vibrations appears at approximately 1470 cm⁻¹. -1 This corresponds to the -CH2- bending vibration, approximately 720 cm. -1 The nearby corresponding long-chain methylene bouncing vibration of polyethylene indicates that the membrane matrix is still composed of low-melting-point polyethylene and other polyolefin structures; approximately 3400 cm -1 A relatively weak and broad peak exists at approximately 1090-1100 cm⁻¹, which can be attributed to the stretching vibrations of Si-OH on the surface of silica and diatomaceous earth, or the OH stretching vibrations of adsorbed water; -1 A strong absorption peak appears nearby, at approximately 800 cm⁻¹. -1 The presence of characteristic peaks nearby, belonging to the asymmetric and symmetric stretching vibrations of Si-O-Si, proves that the silicon-oxygen structure in the in-situ coated low-melting-point polyethylene / silica composite particles and diatomaceous earth has been introduced into the membrane system; in addition, approximately 1730 cm⁻¹ -1 The weak peaks nearby may originate from the ester C=O group or a small amount of oxidized carbonyl structure in the silane coupling agent. The spectrum indicates that the polyolefin matrix, silicon-oxygen inorganic network, and silane interface modified structure coexist in the membrane, consistent with the compositional characteristics of low-closed-pore, high-breakage polyolefin membranes.
[0065] Example 2 The preparation of a low-closed-cell, high-breakage polyolefin membrane is carried out by referring to the preparation method in Example 1, except that 15 parts of the in-situ coated low-melting-point polyethylene / silica composite particles are replaced with 10 parts, and the rest remains the same as in Example 1.
[0066] Example 3 The preparation of a low-closed-cell, high-breakage polyolefin membrane is carried out by referring to the preparation method in Example 1, except that 15 parts of the in-situ coated low-melting-point polyethylene / silica composite particles are replaced with 20 parts, and the rest remains the same as in Example 1.
[0067] Example 4 The preparation of a low-closed-cell, high-breakage polyolefin membrane is carried out by referring to the preparation method in Example 1, except that 10 parts of diatomaceous earth are replaced with 15 parts, and the rest remains the same as in Example 1.
[0068] Comparative Examples 1-5 The preparation of a low-closed-cell, high-breakage polyolefin membrane was carried out by referring to the preparation method in Example 1, except that the in-situ coated low-melting-point polyethylene / silica composite particles were replaced with the in-situ coated low-melting-point polyethylene / silica composite particles prepared in Comparative Preparation Examples 1-5, and the rest remained the same as in Example 1.
[0069] Comparative Example 6 The preparation of a low-closed-cell, high-breakage polyolefin membrane is carried out by referring to the preparation method in Example 1, except that the in-situ coated low-melting-point polyethylene / silica composite particles are replaced with low-melting-point polyethylene resin, and the rest is the same as in Example 1.
[0070] Comparative Example 7 The preparation of a low-closed-cell, high-breakage polyolefin membrane follows the same method as in Example 1, except that the in-situ coated low-melting-point polyethylene / silica composite particles are replaced with conventional high-density polyethylene resin, while the rest remains the same as in Example 1.
[0071] Comparative Example 8 The preparation of a low-closed-cell, high-breakage polyolefin membrane follows the same method as in Example 1, except that the in-situ coated low-melting-point polyethylene / silica composite particles are not added, and everything else remains the same as in Example 1.
[0072] Performance testing: 1. Tensile strength: Tested according to GB / T1040.3-2006, and the data are shown in Table 1.
[0073] 2. Air permeability: Tested according to GB / T36363-2018, in a test environment with a temperature of (23±2)℃ and a relative humidity of (50±5)%RH, using a Gurley air permeability tester, under a constant pressure difference of 1.21kPa, the permeable area of 100mL of air was measured to be 6.45cm². 2 The time required for the diaphragm sample is expressed in seconds per 100 mL, and the data are shown in Table 1.
[0074] 3. Closed-cell temperature: Determined according to GB / T36363-2018 and the industry-standard simulated battery resistance mutation method. The separator to be tested was cut to a size matching the positive and negative electrodes and assembled with lithium metal electrodes and a standard electrolyte (1 mol / L LiPF6 / EC+DMC+EMC, volume ratio 1:1:1) to form a simulated test battery. The battery was placed in a programmable temperature-controlled oven and heated from 30℃ to 200℃ at a heating rate of (2±0.5)℃ / min, while simultaneously and continuously recording the battery temperature and corresponding internal resistance values, and plotting a temperature-resistance curve. The temperature at which the resistance increase first exceeds 50Ω was recorded as the closed-cell temperature. The separator to be tested was then assembled with lithium metal electrodes and a standard electrolyte to form a simulated test battery, and heated from 30℃ to 220℃ at a heating rate of (2±0.5)℃ / min, while simultaneously recording the change in battery internal resistance. When the diaphragm forms a high-resistance state in the closed pores, the internal resistance suddenly drops and short-circuit characteristics appear. The corresponding temperature is recorded as the rupture temperature, and the data is shown in Table 1.
[0075] 4. Electrolyte absorption rate: determined by immersion weighing method. A 50mm × 50mm sample was cut and vacuum dried at (105±2)℃ for 2 hours. After removal, it was placed in a desiccator and cooled to room temperature. The dry weight m0 (g) was measured. The sample was completely immersed in standard electrolyte (1mol / L LiPF6 / EC+DMC+EMC, volume ratio 1:1:1) and sealed at (25±2)℃ for 2 hours. After removal, the free electrolyte on the surface was gently absorbed with filter paper, and the wet weight m1 (g) was quickly measured. The electrolyte absorption rate was calculated as follows: Electrolyte absorption rate / % = [(m1-m0) / m0] × 100%. The data are shown in Table 1.
[0076] Table 1. Performance test data of the examples and comparative examples
[0077] As shown in Table 1, the embodiments exhibit superior overall performance, achieving both lower pore-closure temperature and higher membrane rupture temperature while maintaining high tensile strength and good electrolyte absorption capacity. This indicates an effective synergy between the in-situ coated low-melting-point polyethylene / silica composite particles and the diatomaceous earth and silane coupling interface system. Specifically, when the composite particle content is moderate, the mechanical strength, thermal safety window, and pore structure stability of the membrane are more balanced. Lower content results in insufficient pore-closure response and high-temperature support, while higher content, although beneficial for pore closure and electrolyte absorption, negatively impacts tensile strength and air permeability uniformity. Increased diatomaceous earth content further enhances high-temperature skeletal support and electrolyte retention capacity, but also increases air permeability resistance and slightly reduces flexibility. In contrast, all comparative examples exhibited varying degrees of overall performance degradation due to the disruption of interface grafting, in-situ coating, dispersion stability, low-melting-point core layer, or overall structure of composite particles. In particular, while the direct use of low-melting-point polyethylene could close the cells earlier, its high-temperature resistance to film rupture and mechanical reliability were significantly insufficient. Without the introduction of low-melting-point composite particles or using conventional high-density polyethylene, it was difficult to obtain a sharp closed-cell response. This indicates that the multiphase synergistic structure formed by the low-melting-point core layer, in-situ silica coating layer, diatomaceous earth support framework, and silane interface bridging in this invention is the key to achieving a balance between low closed-cell performance, high film rupture performance, and good mechanical properties.
[0078] Although embodiments of the invention have been shown and described, it will be understood by those skilled in the art that various changes, modifications, substitutions and alterations can be made to these embodiments without departing from the principles and spirit of the invention, the scope of which is defined by the appended claims and their equivalents.
Claims
1. A low-closed-cell, high-breakage polyolefin separator, characterized in that, The solid matrix of the diaphragm is composed of the following components in parts by weight: 50-80 parts of high-density polyethylene, 10-25 parts of in-situ coated low-melting-point polyethylene / silica composite particles, 5-15 parts of diatomaceous earth, 0.5-2 parts of silane coupling agent, 0.5-2 parts of antioxidant, and 1-3 parts of lubricant. The in-situ coated low-melting-point polyethylene / silica composite particles are prepared from the following raw materials in parts by weight: 100 parts of low-melting-point polyethylene resin with a melting point of 120-125℃, 3-5 parts of vinyltrimethoxysilane, 0.03-0.08 parts of benzoyl peroxide, 0.3-0.8 parts of polyvinylpyrrolidone, 40-60 parts of tetraethyl silicate, 2-4 parts of ammonia water with a mass concentration of 25%, 400-600 parts of anhydrous ethanol, and 80-150 parts of deionized water.
2. The low-closed-cell, high-breakage polyolefin separator according to claim 1, characterized in that, The preparation method of the in-situ coated low-melting-point polyethylene / silica composite particles includes the following steps: S1. Cryogenic phase change pulverization: The low-melting-point polyethylene resin is pre-cooled in a liquid nitrogen environment for 20-40 minutes to reduce the material temperature to below -150℃. Then, cryogenic impact pulverization and airflow classification are performed to collect low-melting-point polyethylene core layer particles with D50 of 0.20-0.40μm and D90 of no more than 0.80μm. S2, Low activation energy interface grafting: 100 parts of low melting point polyethylene core layer microparticles obtained in S1, 3-5 parts of vinyltrimethoxysilane and 0.03-0.08 parts of benzoyl peroxide are added to a high-speed mixing system. Under nitrogen protection, the mixture is sheared at a speed of 3000-5000 rpm for 30-45 minutes, and the material temperature is controlled at 80-90℃ to obtain activated microparticles with hydrolyzable silane groups on the surface. S3. Stable interfacial dispersion: The activated microparticles are added to a mixture of anhydrous ethanol and deionized water, wherein the volume ratio of anhydrous ethanol to deionized water is 4:1, and 0.3-0.8 parts of polyvinylpyrrolidone are added. After ultrasonic dispersion at 25-35℃ for 20-40 min, the mixture is stirred at 600-1000 rpm for 30-60 min to obtain a stable dispersion. S4. Low-temperature in-situ copolymerization coating: Add 40-60 parts of tetraethyl silicate to the stable dispersion dropwise over a period of 30-60 minutes. After the addition is complete, add 2-4 parts of ammonia water with a mass concentration of 25% to adjust the pH of the system to 8.5-9.
5. Perform ultrasonic-assisted stirring at 35-45°C for 4-6 hours to hydrolyze and condense tetraethyl silicate to form a silica network. Then, through the silane grafting layer on the surface of the activated microparticles, a continuous silica coating layer is grown in situ on the surface of the low-melting-point polyethylene core layer. S5. Thermal densification treatment: The reaction solution obtained in S4 is spray-dried, with the inlet air temperature being 85-95℃ and the outlet air temperature being 55-70℃, to obtain primary composite particles; then the primary composite particles are placed at 85℃ and under a vacuum degree of less than -0.09MPa for 20-24 hours to obtain the in-situ coated low melting point polyethylene / silica composite particles.
3. The low-closed-cell, high-breakage polyolefin separator according to claim 1, characterized in that, The diatomaceous earth has a median diameter of 8-14 μm, an oil absorption rate of 80%-160%, and a moisture content of ≤0.5% by mass. The density of the high-density polyethylene is 0.950-0.960 g / cm³. 3 The melt flow rate at 190℃ and 2.16kg is 0.1-0.5g / 10min.
4. The low-closed-cell, high-breakage polyolefin separator according to claim 1, characterized in that, The antioxidant is a compound of pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate] and tris(2,4-di-tert-butyl)phosphite in a mass ratio of 1:
1.
5. The low-closed-cell, high-breakage polyolefin separator according to claim 1, characterized in that, The lubricant is a compound of calcium stearate and ethylene bis-stearamide mixed in a mass ratio of 1:
2.
6. The low-closed-cell, high-breakage polyolefin separator according to claim 1, characterized in that, The silane coupling agent is 3-(methacryloyloxy)propyltrimethoxysilane.
7. A low-closed-cell, high-breakage polyolefin separator according to claim 2, characterized in that, The low-melting-point polyethylene resin in S1 is metallocene polyethylene, with a density of 0.910-0.925 g / cm³. 3 .
8. A low-closed-cell, high-breakage polyolefin separator according to claim 2, characterized in that, The free radical initiator in S2 is benzoyl peroxide.
9. A method for preparing a low-closed-cell, high-breakage polyolefin separator according to any one of claims 1-8, characterized in that, Includes the following steps: (1) Material mixing: Add high-density polyethylene, in-situ coated low-melting-point polyethylene / silica composite particles, diatomaceous earth, silane coupling agent, antioxidant and lubricant to a high-speed kneader and mix at 110-120℃ for 10-15 minutes. (2) Melt extrusion: The mixed material is added to a twin-screw extruder, and after melt blending, extrusion and casting, a base film is obtained. (3) Annealing treatment: Anneal the base film in a hot air oven at 105-115℃ for 1-2 hours. (4) Biaxial stretching: The annealed base film is stretched longitudinally and transversely in sequence. (5) Heat setting: The stretched film is heat set at 120-130℃, and the diaphragm is obtained after cooling and winding.
10. The method for preparing a low-closed-cell, high-breakage polyolefin separator according to claim 9, characterized in that, The temperature of each zone of the twin-screw extruder in step (2) is set as follows: feeding zone 160-170℃, melting zone 190-210℃, metering zone 200-220℃, and die head zone 195-205℃. In step (4), the longitudinal stretching temperature is 85-95℃ and the stretching ratio is 4-6 times; the transverse stretching temperature is 100-110℃ and the stretching ratio is 3-5 times.